Menumbuhkan Literasi Kewirausahaan Menuju Kemandirian Pemuda Karang Taruna Desa Jatidrojog - Tri Winarsih; Muhammad Dzikri Abadi; Sindi Mei Setyawati; Anissa Amaliya (JURNAL AKADEMIK PENGABDIAN MASYARAKAT, 2024)
The existence of a large nation cannot be separated from the problem of unemployment. Eradicating unemployment will not be resolved immediately, but with high commitment to the policies taken by the government it can reduce the number of unemployed. Entrepreneurial Literacy is promoted in creating youth independence to reduce the existence of unemployment. Jatidrojog Village, which contains mostly elderly people with a background mostly as farmers, and seeing the potential for many young people who do not have jobs (unemployed), inspired researchers to provide education on the importance of entrepreneurial literacy at a young age, namely by providing training to young people from the Jatidrojog Village Youth Organization. through lecture and discussion methods as well as implementation of practices and solutions in fostering youth independence. The aim of this community service is that it is hoped that the young people of Jatidrojog Village will understand the importance of entrepreneurial literacy before starting an entrepreneurial business, so that with the involvement of young people in the entrepreneurial field, the youth's independence in pursuing this business field can be utilized by the surrounding community.